The Effect of Training Methods on the Dominance of Type I and Type II Muscle Fibers: An Evidence-Based Systematic Review - Arga Arga; Arif Ardian Arfah (International Journal of Experimental Sports Science Research, 2026)
Background: Muscle fiber type composition is a key determinant of physical performance, health, and sports specialization. Training modality whether endurance, resistance, high-intensity interval (HIIT), or plyometric has been shown to induce specific adaptations in Type I (slow-twitch) and Type II (fast-twitch) muscle fibers through distinct molecular and histological pathways. Objectives: This narrative review aims to systematically analyze scientific evidence regarding the influence of various training methods on the dominance of Type I and Type II muscle fibers, covering the underlying mechanisms and implications for sports science practice. Methods: A literature review was conducted using electronic databases including Google Scholar, PubMed, and Scopus, with publication years ranging from 2015 to 2025. Studies involving human subjects with intervention periods of at least 4 weeks and fiber type analysis via muscle biopsy or myosin heavy chain (MHC) isoform identification were included. Results: Endurance training consistently shifts fiber composition toward Type I dominance via PGC-1α/AMPK signaling and mitochondrial biogenesis, while high-load resistance training primarily induces Type II hypertrophy. HIIT and sprint interval training promote Type IIa fiber dominance and hybrid fiber development. Plyometric training selectively enhances Type IIx and IIa recruitment. Detraining reverses these adaptations. Conclusions: Different training methods produce distinct, evidence-based adaptations in muscle fiber type composition. Understanding these shifts is critical for designing sports-specific training programs and optimizing athletic performance.